The young Levinas between two modes of "understanding of spirituality" in the interwar philosophy - Pablo Facundo Ríos Flores (Revista de Filosofia, 2018)
In the 1920s, Emmanuel Levinas was captivated by the new understanding of the existence of the Heideggerian ontologism in his struggle against the Ernst Cassirer´s Neo-Kantian philosophy. However, this initial fascination vanished after Nazism´s rise to power and Heidegger’s adherence to the new National Socialist Regime. The present article aims to analyze the dramatic displacement of Levinas from his early attraction by existential hermeneutics until his later critical separation.